Hubungan antara Pengendalian Lahan Pertanian dan Penyediaan Tanah untuk Perumahan di Yogyakarta - Susilo Widiyantoro; Agam Marsoyo; Kawik Sugiana (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
The increasing number of agricultural land conversion becomes residentials in Yogyakarta become the indicator of ineffectiveness on agricultural land use control. The objectives of this research are (1) modeling the existence of agricultural land use control, (2) modeling the process of residential land occupation, and (3) the agricultural land use control associated with the process of land occupation for residentials. The locus of this research is residential, with an area of at least 2 (two) Ha in the Yogyakarta Urban Area. The overlaying method was used to identify the land-use change and the qualitative inductive as a method in this research used to record the process of agricultural land use control and the process of residential land occupation. The results show that (1) the agricultural land-use control instrument model refers to the local spatial land use planning, (2) there are five stages on the process of land occupation carried out by developers, and (3) each of agricultural land use control instruments is related to the process of land occupation. Based on the three mentioned conditions, it can be concluded that there is no enthusiasm for controlling agricultural land at the regional level, and commitment is needed between the government and all stakeholders to realize agricultural land use control as mandated in the regulations.Keywords: agricultural land use control, land occupation, residentialIntisari: Peningkatan angka konversi lahan pertanian menjadi perumahan di Yogyakarta adalah salah satu indikator tidak efektifnya pengendalian lahan pertanian pangan. Tujuan penelitian ini adalah (1) pemodelan pengendalian lahan pertanian yang selama ini terjadi, (2) pemodelan penyediaan tanah untuk perumahan-perumahan yang dilakukan oleh pengembang, dan (3) keterkaitan antara pengendalian lahan pertanian dengan keberadaan perumahan-perumahan. Lokus penelitian ini adalah perumahan-perumahan dengan luasan minimal 2 (dua) Ha yang berada di dalam zona Kawasan Perkotaan Yogyakarta. Metode yang digunakan adalah overlay peta penggunaan tanah untuk mendapatkan pola perubahan guna lahan dan induktif kualitatif untuk mendapatkan alur pengendalian lahan pertanian dan penyediaan tanah perumahan. Hasil penelitian menunjukkan bahwa (1) model instrumen pengendalian lahan mengacu pada dokumen rencana tata ruang wilayah setempat; (2) terdapat lima tahapan dalam penyediaan tanah yang dilakukan oleh para pengembang perumahan; dan (3) masing-masing instrumen pengendalian memiliki keterkaitan dengan alur penyediaan tanah yang terjadi. Dari ketiga kondisi tersebut disimpulkan bahwa tidak ada semangat pengendalian lahan pertanian di tingkat daerah dan dibutuhkan komitmen antara pemerintah dan seluruh stakeholder untuk mewujudkan pengendalian lahan pertanian pangan sebagaimana diamanatkan dalam undang-undang.Kata kunci: pengendalian lahan pertanian, penyediaan tanah, perumahan